The Green Economy Transformation in Rural Agrotourism - Divanda Rahmaddiono Putra; M. Thoha Ainun Najib (Journal Creative Economics and Trading Halal Ecosystem, 2026)
This study examines the implementation of green economy principles in Green Garden Magetan, an agrotourism area located in East Java, Indonesia, by integrating environmental sustainability with Islamic economic ethics. Using a qualitative field research approach, data were collected through interviews, observations, and documentation involving managers, local residents, and visitors. The analysis employed the Miles and Huberman interactive model and triangulation to ensure validity. Findings show that the transformation toward a green economy has produced positive environmental outcomes, including organic waste recycling, water efficiency, and land revitalization; social benefits through community participation and skill development; and economic gains through profit-sharing and business diversification. However, challenges persist in equitable income distribution, green infrastructure, and tourist environmental awareness. This study highlights that integrating maqāṣid al-syarī‘ah values justice (‘adl), stewardship (khilāfah), and environmental preservation (ḥifẓ al-bī’ah) enhances the ethical dimension of sustainability. The research concludes that the Green Garden model offers a replicable framework for Islamic based green economy transformation in rural agrotourism, aligning local development with the Sustainable Development Goals (SDGs).